How Small-Medium Enterprises Leverage Intangibles During Recessions. Evidence from the Italian Clothing Industry. Issue 8 (20th August 2014) - Cucculelli, Marco; Bettinelli, Cristina; Renoldi, Angelo
Abstract : Purpose: This paper focuses on how investments in research and development (R&D) and advertising affect the performance of small and medium-sized enterprises (SMEs) during recessions. Design/methodology/approach: Contingency theory is applied to a dataset of 376 Italian clothing SMEs during the period 2000-2010 to test whether investment in R&D and advertising impacts financial performance differently when contingent factors (such as market share, financial leverage and business model change) are taken into account. Findings: Empirical results confirm that market share and leverage moderate the effects of investments in R&D and advertising (i.e. intangibles) on performance, and also that changes in business models are an important contingent factor that explains performance. Specifically, the paper ascertains that a novelty-centered business model, together with investments in intangibles, positively affects performance during recessions. Originality/value: This study offers an input to the debate on how SMEs develop and sustain their competitive advantage during the recession. It contributes to existent theory by showing whether and how contingencies, such as a firm's market share and leverage, moderate the relationship between performance and investments in R&D and advertising in SMEs. Second, it addresses the call for additional data 'about the strategic effects of business models and how they influence the positioning of firms in their competitive environment' (Amit and Zott, 2008:20) by introducing business model change/innovation as a new contingency factor and by empirically testing its effects on 'objective measures of firm performance' (Bock, Opsahl, George, and Gann, 2012:301).